2006
DOI: 10.1016/j.ejpain.2005.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ischemic pain attenuates somatosensory evoked potentials induced by electrical tooth stimulation: Diffuse noxious inhibitory controls in the trigeminal nerve territory

Abstract: The purpose of this study was to determine whether the late component of somatosensory evoked potentials (SEP) induced by electrical tooth stimulation and pain intensity are inhibited by heterotopic ischemic stimulation. The tourniquet pressure with 50 mmHg greater than the individual's systolic pressure was applied to the left upper arm for 10 min as ischemic conditioning stimulation. The late component of SEP and visual analogue scale (VAS) were recorded at 4 times and both were significantly decreased when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 52 publications
6
63
2
Order By: Relevance
“…The heterotopic character of endogenous analgesia in the spinal system has been demonstrated psychophysically [26,37,53] and electrophysiologically [2,7,13,39,41,53] in healthy volunteers [18,54] and patients with neurogenic pain [4]. Decreased overall inhibition, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterotopic character of endogenous analgesia in the spinal system has been demonstrated psychophysically [26,37,53] and electrophysiologically [2,7,13,39,41,53] in healthy volunteers [18,54] and patients with neurogenic pain [4]. Decreased overall inhibition, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The cold pressor resulted in greater pain intensity than the muscle pain, and also greater DNIC suggesting that greater pain during the DNIC induction stimulus results in greater DNIC. However, the literature is not clear on whether there is a relationships between the intensity of the tonic stimulus and the magnitude of DNIC with some studies showing that the greater the pain intensity the greater the DNIC [13,29,49] while others do not show this relationship [3,38]. It is not clear if the different results can be explained by the different stimulus paradigms applied.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of order was possibly due to an after-effect of conditioning stimulation. Previous research reported decreased pain and somatosensory evoked potentials 5 minutes after termination of the conditioning stimulation compared to a control condition 41. There was a 5-minute interval between the end of the last conditioning stimulation trial, and the onset of the first test stimulus alone trial.…”
Section: Discussionmentioning
confidence: 98%
“…The magnitude of CPM is measured by the change from baseline in the test stimulus to after the conditioning stimulus is applied. The CPM effect appears to peak during the application of the conditioning stimulus and fades rapidly from 5 to 10 minutes after the conditioning stimulus ceases [43, 53, 101, 102]. One report indicates that the approximate median magnitude of CPM represents about a 29% decrease in pain rating, regardless of the test stimulus used [43].…”
Section: Dynamic Quantitative Sensory Testingmentioning
confidence: 99%